The effect of curcumin on liver fibrosis in the rat model of microsurgical cholestasis. Issue 7 (8th July 2015) - Barta, Andrej; Janega, Pavol; Babál, Pavel; Murár, Erich; Cebová, Martina; Pechánová, Olga
<x xml:space="preserve">Abstract</x> We aimed to determine the effects of curcumin on liver fibrosis and to clarify the role of nuclear factor-κB (NF-κB) and inducible nitric oxide synthase (iNOS) in a model of microsurgical cholestasis in the early stage of extrahepatic biliary atresia.